The Britannia and Conway tubular bridges : with general inquiries on beams and on the properties of materials used in construction. Vol. 2 - Clark, Edwin, 1814-1894 (Day ; John Weale, 1850)
This title includes descriptions of the circumstances leading to the building of the Britannia and Conway bridges, the preliminary design tests undertaken, and the floating and raising operations. It goes on to expound the theory of beams, to investigate the strength of materials used in construction, and to give an account of tidal observations made at the works.
Includes index.
Keywords: Tubular bridges.; Britannia Bridge (Wales); Conway bridge (Wales); elektronické knihy; electronic books